2021
DOI: 10.1136/bmjebm-2020-111634
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of direct oral anticoagulants (DOACs) versus vitamin K antagonists (VKAs) for stroke prevention in patients with atrial fibrillation: a systematic review and meta-analysis

Abstract: ObjectivesTo assess cost-effectiveness of direct oral anticoagulants (DOACs) compared with vitamin K antagonists (VKAs) for stroke prevention in atrial fibrillation (AF) by pooling incremental net benefits (INBs).DesignSystematic review and meta-analysis.SettingWe searched PubMed, Scopus and Centre for Evaluation of Value and Risks in Health Registry from inception to December 2019.ParticipantsPatients with AF.Main outcome measuresThe INB was defined as a difference of incremental effectiveness multiplied by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 134 publications
0
7
0
1
Order By: Relevance
“…The guideline also recommends that catheter ablation be reserved in patients with AF who remain symptomatic despite optimal medical therapy [ 1 ]. In MICs, a meta-analysis showed that DOACs were not cost effective compared with VKA [ 71 ], but in HICs, DOACs were cost effective. In cardiac rhythm control, a systematic review showed that catheter ablation was not cost effective as a first line compared with AAD as there was insufficient evidence to support the superiority of catheter ablation over AAD [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…The guideline also recommends that catheter ablation be reserved in patients with AF who remain symptomatic despite optimal medical therapy [ 1 ]. In MICs, a meta-analysis showed that DOACs were not cost effective compared with VKA [ 71 ], but in HICs, DOACs were cost effective. In cardiac rhythm control, a systematic review showed that catheter ablation was not cost effective as a first line compared with AAD as there was insufficient evidence to support the superiority of catheter ablation over AAD [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“… 38 Disparity on the developmental stages of the health system among high-income countries versus LMIC can potentially lead to differences in drug performance. 39 , 40 As a result, a cost effectiveness analysis may be more applicable to a health system if the local data are used as input parameters. 41 Real-world evidence has been recognized for its strength in answering the actual questions based on real-world data and widely encouraged in informing treatment reimbursement decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, significant differences exist in the developmental stages of high-income and low- and middle-income countries. This disparity can cause variability in the performance of fibrinolytics in both regions [ 72 , 73 ]. Due to the shortage of data and conflicting outcomes of several studies regarding the safety and efficacy of TNK vs SK, this systematic review was carried out to establish which thrombolytic is superior in managing MI in the emerging world.…”
Section: Reviewmentioning
confidence: 99%